Asthma mortality in Brazil, 1980-2012: a regional perspective - Thaís de Sá Brito; Ronir Raggio Luiz; José Roberto Lapa e Silva; Hisbello da Silva Campos (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: To estimate asthma mortality rates in Brazil for the period 1980-2012. Methods: On the basis of data from the Brazilian National Ministry of Health Mortality Database, we estimated mortality rates by calculating moving averages from a municipal perspective that would allow an evaluation differentiating between urban, rural, and intermediate (rurban) Brazil during the period 2002-2012. Trends were assessed using simple linear regression. Results: On average, 2,339 asthma-related deaths were reported per year during the study period. Asthma ranged from the 53rd to 95th leading cause of death. There was a decrease in asthma mortality rates in the country, from 1.92/100,000 population in 1980 to 1.21/100,000 population in 2012. From the municipal perspective, rates fell in urban and rurban Brazil, but increased in rural Brazil, except in the 5-34-year age group. Asthma mortality rates fell in the population under 25 years of age and increased among those over 74 years of age. Rates were always higher in females. Conclusions: Asthma mortality rates in Brazil have been decreasing slightly, with the decrease being more marked in the decade 2002-2012. Only the northeastern region of Brazil showed the opposite trend. Asthma mortality rates in urban and rurban Brazil showed a downward trend similar to that of the national scenario, whereas rural Brazil showed the opposite behavior. Analysis by age group showed that rates decreased among younger individuals and increased among the elderly aged ≥ 75 years.